Amelioration of anxiety, depression, and chemotherapy related toxicity after crocin administration during chemotherapy of breast cancer: A double blind, randomized clinical trial. (24th June 2021) - Salek, Roham; Dehghani, Mansoureh; Mohajeri, Seyed Ahmad; Talaei, Ali; Fanipakdel, Azar; Javadinia, Seyed Alireza
Abstract : The effects of saffron ( Crocus sativus L.) on mood disorders have already been established. More recently, its anti‐neoplastic effects have provoked a great attention. This study aims to assess the effects of crocin administration during doxorubicin‐based chemotherapy of breast cancer on anxiety, depression, and chemotherapy toxicity profile. Seventy‐two patients with non‐metastatic Her2/neu positive or triple negative breast cancer were enrolled and randomly assigned to receive either 30 mg/day of crocin or placebo during chemotherapy [2:2]. Beck's Depression and Anxiety Inventories were used at baseline and end of the trial. In addition, the ECOG Common Toxicity Criteria were applied to assess chemotherapy side‐effects. After the intervention, the degree of anxiety and depression decreased significantly in the crocin group ( p  = .001 for both) and increased significantly in the placebo‐group ( p  = .006 and p  = .036, respectively). There were significantly higher grade II‐IV leukopenia (47.2% vs. 19.4%, p  = .012) in the crocin group, and grade II‐IV hypersensitivity‐reaction (30.6% vs. 5.6%, p  = .006) in addition to neurological disorders (66.7% vs. 41.7%, p  = .03) in the placebo‐group. The results indicate that using crocin during chemotherapy in patients with breast cancer has ameliorated anxiety and depression. Moreover, leucopenia increased whereas hypersensitivity reaction and neurological disorders decreased in the crocin group. In addition, a trend toward survival improvement was observed, which is going to be investigated on longer follow up.